Pengaruh Green Intellectual Capital terhadap Sustainability Reporting Disclosure dengan Gender sebagai Variabel Moderasi - Chavid Al Amin; Vinola Herawaty (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of Green Intellectual Capital Disclosure on Sustainability reporting disclosure with Gender as a moderating variable. The samples in this research are companies that are included in the Healthcare and Consumer Non-Cyclicals sector companies listed on the IDX for the 2021-2022 period. This research was taken using quantitative methods and obtained a total population of 158 companies in the Healthcare & Consumer Non-Cyclicals Sector. Of the 158 manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2021-2022, only 67 companies met the sampling criteria. These results show that Green Human Capital and Gender relations with Green relation capital have a positive effect on Sustainability reporting disclosure, while Green Structural Capital, Green Relations Capital, Gender relations with Green Human Capital, Gender relations with Green Structural Capital and Gender do not have a positive effect on Sustainability reporting disclosure.